MENINGKATKAN MUTU PENDIDIKAN MELALUI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) - Siti Nurhasanah; Elvira Sitna Hajar; Imam Subhi (Universitas Islam Depok, 2021)
One of the educational problems faced by the Indonesian people is the low quality of education at every level and unit of education, especially primary and secondary education. The 21st century is a momentum full of challenges for developing countries like Indonesia. The existence of integrated quality management in education is not a management strategy that appears suddenly, but has been motivated by the development of scientific management, and the development of the industrial world in Japan, America and England. When we talk about School-Based Quality Improvement Management (MPMBS), it cannot be separated from total quality management in education which is often referred to as total quality education (TQE). Therefore, to improve the quality of education in schools, it is necessary to implement integrated quality management in education and MPMBS is a part of it.